Effects of Insider Trading on Abnormal Return : Evidence from the Finnish Stock Market between the years 2017–2021 - Craelius, Niklas (My University, 2025)
This thesis examines the informational value of insider trading announcements in the Finnish stock market during the period from 2017 to 2021, following the introduction of the Market Abuse Regulation (MAR) in 2016. Specifically, it investigates whether insider trades generate significant cumulative abnormal returns (CAR), explores variations in CAR across different subsamples, and assesses the feasibility of mimicking insider trading as a profitable investment strategy. The analysis employs event study methodology, using the market model to estimate abnormal returns around insider trading dates, with event windows of +3, +30, and +60 trading days following the transaction. Additionally, ordinary least squares (OLS) regression is applied to explore differences in CARs across industry sectors, calendar quarters, and trade sizes. The results indicate that insider purchases in the Finnish market yield statistically significant positive abnormal returns, particularly pronounced within the shortest event window (+3 days). However, the economic magnitude of these returns remains modest, generally below 1%. Subsample analysis reveals notable heterogeneity across sectors, with the Real Estate and Basic Materials sectors consistently exhibiting significant positive returns. Quarterly analyses highlight increased abnormal returns during the third quarter, suggesting potential seasonal effects. Furthermore, trade size analysis indicates a positive relationship between trade magnitude and abnormal returns, although the returns remain economically limited. Considering transaction costs, information lags due to regulatory reporting requirements, and limited time frames, the practical feasibility of replicating insider trades as a profitable strategy for retail investors appears limited. For future research, extending the estimation window and examining the effect of analyst coverage on insider trading returns could be beneficial.

Tämä pro gradu -tutkielma tarkastelee vuosina 2017–2021 toteutettujen sisäpiirikauppojen informaatiovaikutusta Helsingin pörssissä. Vuosi 2017 valittiin tutkimuksen aloitusajankohdaksi voimaan astuneen markkinoiden väärinkäyttöasetuksen (MAR) aiheuttamasta merkittävästä muutoksesta sisäpiirinkaupankäynnin raportoinnissa. Tutkimuksen tavoitteena on selvittää synnyttävätkö sisäpiirikaupat merkittäviä kumulatiivisia epänormaaleja tuottoja (CAR) ja tarkastella CAR-arvojen vaihtelua eri osajoukoissa sekä arvioida onko sisäpiirin ostojen jäljittely piensijoittajan kannalta kannattava sijoitusstrategia. Tutkimusmetodina käytetään tapahtumatutkimusta, sekä markkinamallia epänormaalien tuottojen arvioimiseksi 3, 30 ja 60 päivää tapahtumaa seuraavina kaupankäyntipäivinä. Lisäksi tutkielmassa sovelletaan tavallista pienimmän neliösumman (OLS) regressioanalyysia CAR- arvojen erojen tutkimiseksi eri toimialoilla, vuosineljänneksillä ja kauppojen suhteellisen koon mukaan jaetuissa osajoukoissa. Tulokset osoittavat, että sisäpiiriläisten ostoja seuraa tilastollisesti merkittäviä positiivisia epänormaaleja tuottoja, erityisesti lyhimmässä kolmen päivän tapahtumaikkunassa. Näiden tuottojen taloudellinen merkitys jää kuitenkin transaktiokulut huomioon ottaen melko vähäiseksi, yleensä alle 1 prosentin. Osajoukkoanalyysi paljastaa merkittäviä eroja eri toimialojen välillä, ja erityisesti kiinteistö- sekä perusmateriaalitoimialat osoittavat johdonmukaisesti merkittäviä positiivisia tuottoja. Kvartaalianalyysi korostaa kolmannen kvartaalin kohonneita epä- normaaleja tuottoja, mikä viittaa mahdollisiin kausivaikutuksiin. Lisäksi yhtiöiden markkina-arvoihin suhteutettujen kauppojen analyysi osoittaa positiivisen yhteyden kaupan koon ja epä- normaalien tuottojen välillä, vaikka epänormaalit tuotot pysyvätkin taloudellisesti rajallisina.
Keywords: Insider trading, abnormal returns, Nasdaq Helsinki, sisäpiirin kaupankäynti, ylituotto, Helsingin pörssi